Older persons with dementia in prison: an integrative review. Issue 1 (16th August 2019) - Peacock, Shelley; Burles, Meridith; Hodson, Alexandra; Kumaran, Maha; MacRae, Rhoda; Peternelj-Taylor, Cindy; Holtslander, Lorraine
Abstract : Purpose: The number of prisoners over 55 years is increasing and many are at risk of developing dementia. This has generated new responsibilities for prisons to provide health and social care for older persons. The purpose of this paper is to synthesize the existing research literature regarding the phenomenon of the health and social care needs of older persons living with dementia in correctional settings. Design/methodology/approach: Using an integrative review method based on Whittemore and Knafl, the inclusion criteria for the review are: articles written in English; a focus on some form of dementia and/or older persons with discussion of dementia; to be set in a correctional context (correctional facility, prison and jail); be derived from a published peer-reviewed journal or unpublished dissertation/thesis; and be a qualitative, quantitative or mixed methods study. Based on those criteria, a search strategy was developed and executed by a health sciences librarian in the following databases: Medline, CINAHL, Embase, PsychINFO, Proquest Nursing and Allied Health and Web of Science; searches were completed up to April 2019. After data were extracted from included studies, synthesis of findings involved an iterative process where thematic analysis was facilitated by Braun and Clarke's approach. Findings: Eight studies met the inclusion criteria. Key findings of the eight studies include recognition of dementia as a concern for correctional populations, dementia-related screening and programming for older persons and recommendations for improved screening and care practices. Most significant is the paucity of research available on this topic. Implications for research are discussed. Originality/value: This paper identified and synthesizes the limited existing international research on the health and social care needs of older persons with dementia living in correctional settings. Although existing research is scant, this review highlights the need for increased awareness of dementia as a concern among older persons living in correctional settings. As well, the review findings emphasize that enhanced screening and interventions, particularly tailored approaches, are imperative to support those living with dementia in correctional settings.